Adductor longus muscle metastasis of transitional cell carcinoma of the urinary bladder. (14th May 2014) - Koca, Irfan; Ucar, Mehmet; Bozdag, Zehra; Alkan, Samet
Abstract : Bladder cancer most commonly spreads to the lymph nodes, lungs, bones and adrenal glands. Metastasis of bladder cancer to the skeletal muscle is extremely rare, as is the case in other malignancies. We report a case of a 62-year-old male patient who presented with pain and swelling in the right lower extremity and had difficulty walking, and who was later found to have metastasis in the adductor longus muscle 3 months after the initial diagnosis of transitional cell carcinoma of the urinary bladder. The study also provides a review of the current literature.